Identity-based domain key distribution protocol in the E-document security management - Xi-xi YAN; Zhao-feng MA; Yi-xian YANG; Xin-xin NIU (Tongxin xuebao)
In order to create a security domain environment in th E-document management,an identity domain key distribution scheme using bilinear pairings for large and dynamic domain was proposed.The scheme could handle the joining and leaving of domain members efficiently,and updateed the domain key in the manner of broadcast,which avoided the complex protocols of key agreement.In addition,the distribution protocol based sharing-domain for E-document was also given,which aimed to realize the function of sharing the documents in a domain and distributing the documents between different domains securely.With the protocol,the E-documents obtained by a domain member could be transmitted to other domain members seamlessly.On the opposite,the E-document which was distributed to another domain need be upload to the server,which would verify the identi in member and encrypt the documents with the specified domain key.